1994
DOI: 10.1093/nar/22.16.3354
|View full text |Cite
|
Sign up to set email alerts
|

A common core structure for U3 small nucleolar RNAs

Abstract: U3 nucleolar small RNA (snRNA) is involved in early processing of the primary rRNA transcript. A secondary structure model for the unusually small Trypanosoma brucei U3 snRNA was deduced by comparative analysis of U3 snRNA sequences and by chemical modification and enzymatic cleavage of U3 snRNA in deproteinized and ribonucleoprotein (RNP) forms. Comprehensive alignment of U3 snRNAs from vertebrate, plant, fungal and protozoan species clearly delineated conserved and divergent features. The 5' domain of the T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 49 publications
2
47
0
Order By: Relevance
“…We did not expect to find that helix 1b9 (nt 47-63) was required for Mpp10p association+ Previous results from studies in several different organisms have implicated only the 39 domain (nt 73 the 39 end) of the U3 snoRNA in protein binding (Parker & Steitz, 1987;Jeppesen et al+, 1988;Segault et al+, 1992;Hartshorne & Agabian, 1994;Mereau et al+, 1997)+ Indeed, the 39 domain of the U3 snoRNA is sufficient for association of the common proteins, Nop56, Nop5/58, fibrillarin, and Snu13p as well as the specific protein, Rrp9p (Lubben et al+, 1993;Pluk et al+, 1998;Lukowiak et al+, 2000;Venema et al+, 2000;Watkins et al+, 2000)+ Because the stem on the distal side of helix 1b9 is protected during chemical and enzymatic mapping in vivo (Segault et al+, 1992;Mereau et al+, 1997), it has been proposed that helix 1b9 may form an additional basepairing interaction with the pre-rRNA+ One possible interpretation of our results is that this interaction is required for Mpp10p association and for overall U3 snoRNP function+ Alternatively, these nucleotides in the U3 snoRNP are protected because Mpp10p and perhaps other proteins are situated there+ Because Mpp10p is found in yeast and metazoans, if the sequence constituting helix 1b9 is truly important for Mpp10p association it would be conserved among different species+ Indeed, phylogenetic comparison of hinge region sequences indicates the capability to form a similar hairpin in the majority of organisms whose sequence is known+ In mammalian U3 snoRNAs, multiple hairpins are even possible+ Of the 20 sequenced U3 snoRNAs from different species, there are only four U3 snoRNAs where no hairpin can be drawn, those from Dictyostelium discoideum, Schizosaccharomyces pombe, Xenopus laevis, and Xenopus borealis+ In general, the sequences that comprise the stem of helix 1b9 are also highly conserved+ For example, two hairpins representing potential helix 1b9 structures can be drawn for the human U3 snoRNA, although the length of the loop differs from that of yeast+ However, although both stem-loop structures in the 59 domain and the hinge region are well conserved, it is thought that they do not form in vivo when the U3 snoRNA is base paired with the pre-rRNA (Mereau et al+, 1997;Antal et al+, 2000)+ Consistent with this is the high level of tolerance of Mpp10p association to mutation of the involved sequences, even to the point of eliminating the helix 1b9 structure+ Conservation, then, of the sequences required for Mpp10p association is likely due to a functional requirement other than maintenance of the structure of helix 1b9+…”
Section: Helix 1b9 Tolerates Extensive Mutations Without Disrupting Mmentioning
confidence: 89%
See 1 more Smart Citation
“…We did not expect to find that helix 1b9 (nt 47-63) was required for Mpp10p association+ Previous results from studies in several different organisms have implicated only the 39 domain (nt 73 the 39 end) of the U3 snoRNA in protein binding (Parker & Steitz, 1987;Jeppesen et al+, 1988;Segault et al+, 1992;Hartshorne & Agabian, 1994;Mereau et al+, 1997)+ Indeed, the 39 domain of the U3 snoRNA is sufficient for association of the common proteins, Nop56, Nop5/58, fibrillarin, and Snu13p as well as the specific protein, Rrp9p (Lubben et al+, 1993;Pluk et al+, 1998;Lukowiak et al+, 2000;Venema et al+, 2000;Watkins et al+, 2000)+ Because the stem on the distal side of helix 1b9 is protected during chemical and enzymatic mapping in vivo (Segault et al+, 1992;Mereau et al+, 1997), it has been proposed that helix 1b9 may form an additional basepairing interaction with the pre-rRNA+ One possible interpretation of our results is that this interaction is required for Mpp10p association and for overall U3 snoRNP function+ Alternatively, these nucleotides in the U3 snoRNP are protected because Mpp10p and perhaps other proteins are situated there+ Because Mpp10p is found in yeast and metazoans, if the sequence constituting helix 1b9 is truly important for Mpp10p association it would be conserved among different species+ Indeed, phylogenetic comparison of hinge region sequences indicates the capability to form a similar hairpin in the majority of organisms whose sequence is known+ In mammalian U3 snoRNAs, multiple hairpins are even possible+ Of the 20 sequenced U3 snoRNAs from different species, there are only four U3 snoRNAs where no hairpin can be drawn, those from Dictyostelium discoideum, Schizosaccharomyces pombe, Xenopus laevis, and Xenopus borealis+ In general, the sequences that comprise the stem of helix 1b9 are also highly conserved+ For example, two hairpins representing potential helix 1b9 structures can be drawn for the human U3 snoRNA, although the length of the loop differs from that of yeast+ However, although both stem-loop structures in the 59 domain and the hinge region are well conserved, it is thought that they do not form in vivo when the U3 snoRNA is base paired with the pre-rRNA (Mereau et al+, 1997;Antal et al+, 2000)+ Consistent with this is the high level of tolerance of Mpp10p association to mutation of the involved sequences, even to the point of eliminating the helix 1b9 structure+ Conservation, then, of the sequences required for Mpp10p association is likely due to a functional requirement other than maintenance of the structure of helix 1b9+…”
Section: Helix 1b9 Tolerates Extensive Mutations Without Disrupting Mmentioning
confidence: 89%
“…The 39 domain of the U3 snoRNA is highly folded and complexed with proteins (Parker & Steitz, 1987;Jeppesen et al+, 1988;Baserga et al+, 1991;Lubben et al+, 1993;Hartshorne & Agabian, 1994;Mereau et al+, 1997;Speckmann et al+, 1999)+ In all U3 molecules, boxes B/C and boxes C9/D are predicted to be in close proximity separated by phylogenetically conserved terminal and central stems+ The remaining nonconserved hairpins of the U3 snoRNA in yeast are dispensable and are not required for U3 function or stability (Samarsky & Fournier, 1998)+ Structural probing of boxes B/C and boxes C9/D in trypanosomes, yeast, and human U3 snoRNPs revealed these boxes are protected and most likely covered with proteins (Parker & Steitz, 1987;Baserga et al+, 1991;Hartshorne & Agabian, 1994;Mereau et al+, 1997)+ In yeast, substitutions of the sequences comprising box B disrupt U3 function (Samarsky & Fournier, 1998)+ In Xenopus, substitution of these same sequences has no affect on function; however, substitution of sequences comprising box C affect function and nucleolar localization of the U3 snoRNA (Lange et al+, 1998)+ Furthermore, mutations in box C affect fibrillarin association with U3 (Baserga et al+, 1991;Lange et al+, 1998;Samarsky & Fournier, 1998;Speckmann et al+, 1999)+ Similarly, fibrillarin has been shown to bind directly to the box C/D sequence of the U16 snoRNA in Xenopus oocytes and in ooycte extracts (Fatica et al+, 2000)+ Substitution of sequences in boxes C9 or D in yeast abolish U3 RNA levels, indicating that these sequences are required for U3 snoRNA accumulation (Samarsky & Fournier, 1998)+ Furthermore, mutations in box D and the 39 terminal stem block cap formation and affect nucleolar localization and nuclear import in Xenopus (Baserga et al+, 1992;Terns et al+, 1995;Lange et al+, 1998)…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of the other sequence elements did not prevent interaction (Fig. 3, U3∆A′, U3∆A, U3∆H, U3∆C′ and U3∆D, lanes [7][8][9][10][11][12][13][14][15][16][17][18][25][26][27]. The results indicate that Boxes B and C of U3 snoRNA are necessary for interaction with U3-55k in vivo.…”
Section: Analysis Of U3 Rna Sequences Required For U3-55k Associationmentioning
confidence: 96%
“…Sequence analysis of U3 snoRNA reveals six evolutionarily conserved sequence elements, termed Boxes A, A′, B, C, C′ and D (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Boxes A and A′ are located in the 5′ domain of U3 snoRNA and, along with the 'hinge' region, base pair to sites within the pre-rRNA to direct the multiple endonucleolytic cleavages necessary for the maturation of 18S rRNA (15,16,23,25,28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation